Lithium Battery SOC Estimation Based on EKF-DEKF Composite Model - Chen, Shaohua; Kan, Wei; Yang, Yichen; Liu, Shuyang; Wang, Miaomiao (Manufacturing Technology Journal, 2023)
According to the application requirements of SOC in lithium batteries of Unmanned Aerial Vehicle (UAV), an Extended Kalman filter-Double Kalman filter (EKF-DKF) composite model was proposed to optimize the accuracy of the last 20% stage of State of Charge(SOC) estimation. Based on the equivalent model of second-order resistance-capacitance (RC) circuit improvement, the developed method optimized the identification accuracy of parameters, and set up a MATLAB simulation platform to jointly estimate SOC online with EKF and DKF. The data obtained in laboratory test environment were used for simulation.
Keywords: Lithium battery; SOC estimation method; Unmanned aerial vehicle; EKF-DKF composite model